Analysis on Students’ Error in Comprehending Elliptical Construction - Tanjung, Khoiriyah Sofiyah (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The purpose of this study is to analyze student errors in comprehending Elliptical Construction material and to explore the most dominant types of errors made by students. The population of this study was first semester of Constitutional Law students at STAIN Gajah Putih Takengon; it consists of two classes and 40 students. The writer takes one class as a sample, namely HTN A. Samples are taken by Random Sampling because both have the same quality and are taught by the same lecturer. Data is collected from students’ answer sheets of English final test. The result of the tests then was analyzed using quantitative descriptive methods. The results showed that there were 122 errors made by students in answering the question of Elliptical Construction. 41% of these errors occur in Disordering, 32% in Misinformation, 19.67% errors in Addition and 13.11% in Omission.